The effect of protein corona composition on the interaction of carbon nanotubes with human blood platelets - De Paoli, Silvia H; Diduch, Lukas L; Tegegn, Tseday Z; Orecna, Martina; Strader, Michael B; Karnaukhova, Elena; Bonevich, John E; Holada, Karel; Simak, Jan (Biomaterials, 2014)
Carbon nanotubes (CNT) are one of the most promising nanomaterials for use in medicine. The blood biocompatibility of CNT is a critical safety issue. In the bloodstream, proteins bind to CNT through non-covalent interactions to form a protein corona, thereby largely defining the biological properties of the CNT. Here, we characterize the interactions of carboxylated-multiwalled carbon nanotubes (CNTCOOH) with common human proteins and investigate the effect of the different protein coronas on the interaction of CNTCOOH with human blood platelets (PLT). Molecular modeling and different photophysical techniques were employed to characterize the binding of albumin (HSA), fibrinogen (FBG), γ-globulins (IgG) and histone H1 (H1) on CNTCOOH. We found that the identity of protein forming the corona greatly affects the outcome of CNTCOOH's interaction with blood PLT. Bare CNTCOOH-induced PLT aggregation and the release of platelet membrane microparticles (PMP). HSA corona attenuated the PLT aggregating activity of CNTCOOH, while FBG caused the agglomeration of CNTCOOH nanomaterial, thereby diminishing the effect of CNTCOOH on PLT. In contrast, the IgG corona caused PLT fragmentation, and the H1 corona induced a strong PLT aggregation, thus potentiating the release of PMP.
Keywords: Cattle; aktivace trombocytů; Animals; Platelet Activation; skot; Biocompatibility; Nanotubes, Carbon; proteom; nanotrubičky uhlíkové; Nanoparticles; trombocyty; povrchové vlastnosti; vazba proteinů; Proteome; lidé; Reactive Oxygen Species; Protein Binding; Blood Platelets; Blood Proteins; Models, Molecular; Platelets; krevní proteiny; L-Lactate Dehydrogenase; Nanotoxicity; molekulární modely; Circular Dichroism; L-laktátdehydrogenasa; reaktivní formy kyslíku; Carbon nanotubes; zvířata; Protein corona; Surface Properties; cirkulární dichroismus; Humans